2013
DOI: 10.1021/ic400308a
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Fast Water Exchange to Slow Molecular Tumbling in Gd3+ Chelates: Why Faster Is Not Always Better

Abstract: The influence of dynamics on solution state structure is a widely overlooked consideration in chemistry. Variations in Gd3+ chelate hydration with changing coordination geometry and dissociative water exchange kinetics substantially impact the effectiveness (or relaxivity) of mono-hydrated Gd3+ chelates as T1-shortening contrast agents for MRI. Theory shows that relaxivity is highly dependent upon the Gd3+-water proton distance (rGdH) and yet this distance is almost never considered as a variable in assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 83 publications
4
76
0
Order By: Relevance
“…6 The difference between that study 6 and this is the presence or absence of one methyl group (Chart 1). The chelates examined in the previous study were exclusively corner isomers.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…6 The difference between that study 6 and this is the presence or absence of one methyl group (Chart 1). The chelates examined in the previous study were exclusively corner isomers.…”
mentioning
confidence: 85%
“…10 However, our work demonstrated that this is not necessarily the case and that water exchange can quite easily be accelerated beyond the point at which it can afford maximum relaxivity. 6 As part of these studies, we noted that substitution of the macrocyclic ring led to the formation of regioisomeric species in the same coordination geometry. 11−13 We had denoted these two regioisomers as "corner" and "side" isomers, depending on the position of the benzylic substitution ( Figure 1).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…As it has been reported that the hydration state (expressed by the q/r 6 value) of Gd(III) in macrocyclic conformers with different water exchange rates is inversely related to the τ M value, 31,32 the analysis was performed using r Gd-H values of 3.0 Å and 3.1 Å for species 1 and 2, respectively. 31 The good quality of the data fitting is an indirect proof that the advantages deriving from a fast water exchange rate are partially limited by a reduced hydration state. The result of the analysis is consistent with the presence of two paramagnetic species with a predominance of the complex with a very short water exchange lifetime (species 2).…”
Section: Preparation and Characterization Of The Mixed Micellesmentioning
confidence: 99%
“…[11] Compared to TSAP, a SAP geometry will result in slower water exchange, but surprisingly a faster relaxation. [12] The comparable size of the macrocyclic cavity of DOTA and TEMDO indicates that suitable metal ions will very well fit to form thermodynamically stable chelates. [13] Qualitative assessment of free lanthanide ions with indicator xylenol orange showed that chelating generally occurs for the lanthanides.…”
mentioning
confidence: 99%